MORE INTERNATIONAL STUDENTS PARTICIPATION SOUGHT FOR NRIC 2015 - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 3 April 2015 – The ViceChancellor of Universiti Sains Malaysia (USM) Professor Dato' Dr. Omar Osman called for more foreign universities’ participation at the upcoming Novel Research Innovation Competition (NRIC) 2015.